Pengaruh Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Dinas Pekerjaan Umum dan Perumahan Rakyat Bidang Perumahan Provinsi Jambi - Wanda Mustikaningrun Pujilestari (Science of Management and Students Research Journal (SMS), 2022)
This study aims to analyze the effect of work discipline on employee performance at the public works office and public housing in the housing sector, Jambi province. In this study the method used is descriptive quantitative method. Quantitative descriptive is data analysis by describing or describing the data that has been collected as it is without intending to make generally accepted conclusions. The population that became the object of this study were employees of the PUPR service office in the Housing Sector of Jambi Province. the method of analysis is regression analysis, hypothesis testing, correlation so the coefficient of determination and t test. Then the analytical method used for testing and proving the hypothesis the authors use descriptive analysis and data management. The results of calculations with SPSS results show that the regression model equation is Y 13,916 + 0.696. From this equation, it can be seen that there is a positive influence between discipline on employee performance. enhancement. Work discipline has a positive and significant effect on employee performance at the PUPR Service Office in the Housing Sector of Jambi Province, which can be seen from the results of the correlation coefficient and determination which state that the magnitude of the constant variable Work Discipline (X) on Employee Performance (Y) is 0.634 or 63.4% categorized Tall.So that with an increase in compensation will improve employee performance. By using the simple regression equation, it can be seen that the significant value is 0.000 > 0,05, this means that Ha is accepted, in other words that the work discipline variable has a significant influence on the performance of the PUPR Service Office employees in the Housing Sector, Jambi Province.